O acesso a documentos arquivísticos produzidos pelas instituições federais de ensino superior: uma abordagem sobre critérios estabelecidos pela lei de acesso à informação - BARATA, Ivana Lúcia Neves de Souza (2017)
The present work aims to realize an analysis about the file management in the Federal Institutions of Higher Education (Institutos Federais de Ensino Superior, IFES) in Belém, observing if the Information Access Law (Lei de Acesso à Informação, LAI) is being applied according to the criteria established by the regulation. The analyzed institutions were the Universidade Federal do Pará – UFPA and the Instituto Federal do Pará – IFPA (Federal University and Institute of Pará). The LAI, as it became known, was officially established on May 16, 2012 and created mechanisms that allow any citizen to receive from the public organs and institutions information registered in the IFES documents. The purpose of this paper is to diagnose the obstacles of file management within the archives of the Federal Institutions of Higher Education, UFPA and IFPA in Belém, as well as observing its application regarded to the regulation standards of said law. The work is divided as follows: Introduction, Problematics and Justification, Objectives, Methodology, Theoretical Reference, LAI Criteria for Access to Documents in IFES; Results, Discussion and Final Thoughts. For study, it was adopted as a methodology the exploratory research with case study and questionnaire application. As a result, it seems that the studied IFES are looking forward to apply the criteria established by the Information Access Law, and given the fact that the regulation is recent in the field of archivology, it is concluded, therefore, that an LAI is a field that needs structure in the IFES archives. Changes begin to occur with the admission of professionals in archivology, being this practice helpful in attending of those who request information e therefore contribute to the transparency of the administrative acts, and assuring the right of citizens to the information contained and registered on documents released by these institutions.